Effectiveness of Synthetic and Natural Antifungals Against Postharvest Diseases and Quality of Barangan Bananas (Musa acuminata) - Aji Mahmudi Tambunan; Aisar Novita; Nor Hanis Aifaa Yusoff (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
This study was conducted to evaluate the effects of antifungal treatments and storage duration on the physical, biochemical, and post-harvest disease quality of Barangan bananas (Musa acuminata). Barangan bananas are a premium agricultural commodity from North Sumatra, popular as table bananas due to their sweet taste and distinctive aroma. Four treatments were applied: kawalan (untreated control), 0.3% cinnamon oil, 200 ppm sodium dichloroisocyanurate (NaDCC), and 200 ppm propiconazole. The parameters evaluated included skin color (brightness, chroma, hue angle), weight loss, texture, pH, citric acid content, total soluble solids (TSS), vitamin C, TSS:TTA ratio, and the severity of crown rot and anthracnose during seven days of storage at room temperature. The results showed that storage duration significantly affected color, weight loss, pH, acidity, and the TSS:TTA ratio, while the treatments did not show significant differences (p > 0.05) for most parameters. However, the 200 ppm propiconazole treatment demonstrated the best performance in maintaining a uniform yellow color, minimizing weight loss, and reducing root rot infection compared to other treatments. Therefore, the use of propiconazole at a moderate concentration is recommended as an effective postharvest treatment for Barangan bananas, suitable for both the local fresh market and medium-term export, especially under non-refrigerated storage conditions.